Summer Preparatory Studies Program - Spartanburg Junior Coll., SC.; Spartanburg Junior Coll., SC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
The growing number of high-risk, culturally deprived students, without adequate pre-college instruction, have little chance of academic success. Spartanburg Junior College, South Carolina, studied several summer preparatory programs and found that they (1) assumed all students started from and arrived at a certain same point in their educational development and (2) did not provide the extra motivation so needed by these easily-discouraged students. Spartanburg developed a preparatory program that assumed (1) every student is gifted in at least one area, (2) no two students are alike in ability or background, (3) careful guidance must accompany academic work, (4) individual adjustment and maturity often predict academic success, and (5) personalized instruction, made possible by technological aids, is the key to intensified learning. The 64 students in the college's summer 1968 program took part in cultural, directed reading, and independent study programs, and received 320 classroom hours distributed among English grammar and composition (110), math (80), reading and comprehension laboratory (80), group dynamics seminar (50). The overall achievement progress averaged 1.4 grade levels; one student advanced 3.0 levels in all areas; another advanced 6.0 levels in one area. No student failed to show progress in all areas. Of the 64 students, 56 were accepted by a college and six returned to high school. The tests, method of evaluation, and detailed results are given. (HH)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Disadvantaged; Remedial Programs; Summer Programs; Two Year Colleges; South Carolina